SISTEM KONTROL INTENSITAS CAHAYA PADA KANDANG PUYUH BERBASIS ARDUINO UNO - -, Ardiyanto; -, Nurfiana (Jurnal Informatika, 2015)
A quail is a type of poultry which producers meat and egg that are rich protein and nutrients in it. Various efforts undertaken to improve the productivity of quail in the scale of cultivation, such as the addition of hormones, feed manipulation, as well as providing additional light with the ultimate goal of optimal growth so that better productivity. Light is one external factor that can spur the growth and control of various biological processes in the body poultry. This researchâs aims are to create a tool that is able to increase the quantity and quality of quail eggs by controlling the light requirements in accordance with the needs of the quail, the illumination using monochromatic light blue by 15-25 lux for 14 hours per day. The method used to made Light Intensity Control System at Quailâs Cage Based-on Arduino Uno, it is starts with collecting information, design tools, making tools, testing tools and conclusions. Based on the results of tests that have been performed on prototype instrument control systems in the light intensity quail cage conclusion that the tool is able to work well in accordance with the design.